Peningkatan Kompetensi Guru dalam Mendesain Project-Based Learning Berbasis Design Thinking untuk Mendukung Pembelajaran Mendalam di Kota Pontianak - Teddy Rianto L Gaol; Erwin Febriansyah; Hilfa Mora Marito Nasution; Muliawati; Sy Ilham Zultami; Risma Carla Lydia Pascasia; Fennika Ayu Lestari; Willyanto; Thia; Arina Azwani (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2026)
The implementation of Deep Learning-oriented education requires teachers to possess the ability to design meaningful, student-centered learning experiences. However, many teachers still encounter challenges in developing innovative learning models that promote critical thinking, creativity, collaboration, and real-world problem solving. This community service program aimed to enhance teachers’ competencies in designing Project-Based Learning (PjBL) integrated with the Design Thinking approach. The program was conducted through a training workshop involving teachers in Pontianak. The activities included pre-test assessment, interactive lectures, discussions, hands-on practice, and project design exercises based on the stages of Design Thinking: empathy, define, ideate, prototype, and test. The results showed increased participants’ understanding of Deep Learning concepts, Project-Based Learning principles, and the application of Design Thinking in educational settings. Participants were able to develop project-based learning plans that addressed students’ needs and contextual challenges. The program contributed to strengthening teachers’ pedagogical competencies and supporting the implementation of meaningful, innovative, and student-centered learning practices. These findings indicate that integrating Design Thinking into PjBL training can serve as an effective strategy for improving the quality of teaching and learning processes.